Pendekatan Pembelajaran IPA Berbasis Sains di Pendidikan Dasar - Putri, Fia Alifah; Lubis, Namiroh; Siregar, Nahrun Najib; Iskandar, Wahyu; Matvayodha, Gupo (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2024)
Natural Science (Science) learning in elementary schools has an important role in forming students' basic understanding of the natural world and the processes that occur in it. Scientific literacy, which includes the ability to read, write and think critically about science, is a crucial component in science learning. This research aims to explore science learning approaches based on scientific literacy in basic education. Using literature study methods and content analysis, this research examines various aspects related to the implementation of scientific literacy in science learning, such as needs analysis, learning models, learning media, as well as the role of teachers and school facilities in supporting scientific literacy. The research results show that a science learning approach based on scientific literacy can improve students' ability to understand scientific concepts, apply them in everyday life, and develop critical thinking skills and decision-making abilities based on scientific evidence.